1983
DOI: 10.1177/019874298300900102
|View full text |Cite
|
Sign up to set email alerts
|

Videotape Feedback as a Behavior Management Technique

Abstract: The effectiveness of videotape feedback, as a procedure for increasing on-task behavior in a 9-year-old emotionally disturbed male, was investigated in the present study. The experimental design employed was an ABAB single subject design. Through baseline (A) and intervention (B) phase, 30 minutes of classroom behavior during a structured activity were videotaped at the same time each day. On-task and off-task behaviors from each videotaped session time were rated by trained observers for each experimental pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…Both Jack and John demonstrated a statistically significant improvement in active engagement once videotaping was introduced and this remained one year later at maintenance. This finding is consistent with a previous study that found an increase in ‘on task’ behaviour after using VFB (Booth & Fairbank, ).…”
Section: Discussionsupporting
confidence: 93%
“…Both Jack and John demonstrated a statistically significant improvement in active engagement once videotaping was introduced and this remained one year later at maintenance. This finding is consistent with a previous study that found an increase in ‘on task’ behaviour after using VFB (Booth & Fairbank, ).…”
Section: Discussionsupporting
confidence: 93%
“…Several particular advantages of providing feedback via videotape have been described in the literature. Booth and Fairbank (1984) suggested that videotapes may provide individuals with more accurate feedback about their behavior. Videotapes also provide a permanent record of behavior; this tends to limit arguments about what transpired, and self-assessment can occur out of the context of any conflicts that may have occurred during taping (Walther & Beare, 1991).…”
Section: Resultsmentioning
confidence: 99%
“…. One intervention that has resulted in improvements in children's social skills combines self-evaluation procedures with the use ofvideotape (e.g., Booth & Fairbank, 1984;DeRoo & Haralson, 1971). In a study by Kern-Dunlap et al (1992), children's peer interactions were improved using a videotape feedback package.…”
mentioning
confidence: 99%